Daily lived experiences of visually impaired learners at a mainstream school in Lesotho - Nthama Matsie; Sindiswa Stofile (International Journal of Studies in Psychology)
Learners with disabilities, particularly the visually impaired face different challenges in their learning encounters. The study explored the daily-lived experiences of visually impaired learners at a mainstream school in Lesotho. A qualitative research approach located in the interpretivist paradigm was adopted. Thirty visually impaired learners were purposefully selected in this study. Data were collected using focus group interviews. The Interpretive Phenomenological Analysis was used to analyse and interpret data. The results showed both rewarding and detrimental daily lived experiences of visually impaired learners in the school setting. On the one hand, rewarding experiences included social interaction, enjoyment of companionship, appreciation, being valued by the school management, a positive relationship with teachers, a sense of belonging to the school, access to inclusive education, participation in extramural activities, and access to educational and psychological resources support. On the other hand, detrimental experiences of the visually impaired learners reported within the inclusive school included unequal opportunities, inadequate assistive technology, inadequate academic support, inappropriate counselling services, hostile learning environments, and physical and psychological violence. We concluded that the inclusion of visually impaired learners needs to be considered to enhance the effective and appropriate implementation of inclusive education. It recommends that the Ministry of Education and Training should make it compulsory for inclusive schools to improve institutional policies with the intention to minimise barriers to learning in institutions of learning.